Backbone rearrangement during olefin capture as the rate limiting step in molecular olefin polymerization catalysis and its effect on comonomer affinity. Issue 17 (4th July 2017) - Zaccaria, Francesco; Cipullo, Roberta; Budzelaar, Peter H. M.; Busico, Vincenzo; Ehm, Christian
ABSTRACT: Available experimental data for several metallocenes indicate that the ethene/propene copolymerization ratio r c can be much more temperature dependent than would be expected if competing insertion transition states (TS) are rate limiting. Detailed exploration of the reaction paths reveals in several cases the existence of a "capture‐like" transition state before the actual insertion, with free energies close to the insertion TS. Movement around these transition states does not just involve monomer and chain, but also clear distortion of the ligand skeleton to allow entry of the monomer. Taking these additional TSs into account leads to much improved agreement with experiment for a series of metallocenes and a constrained geometry catalyst system. Depending on catalyst and temperature, selectivity is determined by competing insertion/insertion, capture/insertion or capture/capture. It seems likely that this is a common situation especially for highly efficient catalysts, complicating (but not preventing) prediction of copolymerization performance. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2807–2814 Abstract : Literature data for several metallocenes indicate that the ethene/propene copolymerization ratio r c can be much more temperature dependent than expected if competing insertion transtion state (TS) are rate limiting. Detailed exploration of olefin insertion reaction paths reveals for several catalysts the existence of a "capture‐like" transition state before the actual insertion, with free energies close to the insertion TS.